When Knowledge Becomes Action: The Relationship Between Ecosystem Concepts and Critical Thinking on Students' Environmental Responsibility - Muhamad Rizal; Supriyatin; Rizhal Hendi Ristanto (Biosfer: Jurnal Pendidikan Biologi, 2026)
Strong knowledge of ecosystem concepts and critical thinking skills are essential for developing environmentally responsible behavior to address contemporary environmental challenges. This behavior ensures that students not only understand ecological solutions but also actively participate in preserving the environment. This study aims to determine the relationship between students' mastery of ecosystem concepts and critical thinking skills with environmentally responsible behavior. Conducted in February 2025 at SMP Shidqia Islamic School with 112 students, the research employed a descriptive method with a correlational design. Data analysis involved prerequisite tests for normality, homogeneity, linearity, and multicollinearity to ensure validity. The findings indicate a moderate correlation between ecosystem concept mastery and environmentally responsible behavior, as well as between critical thinking skills and environmental responsibility. Furthermore, a simultaneous correlation exists when both ecosystem mastery and critical thinking skills are combined. It is recommended that biology educators integrate critical thinking exercises within ecological curriculum to effectively foster students' environmental responsibility. School policies should prioritize the implementation of active learning models that effectively bridge theoretical ecological knowledge into tangible and sustainable environmentally responsible behaviors within the educational ecosystem.